Efektivitas dan Kontribusi Pajak Daerah dalam Meningkatkan Pendapatan Asli Daerah Kota Bekasi - Kayla Jasmine Andira; Etty Gurendrawati; Muhammad Yusuf (LPPM Universitas Negeri Jakarta, 2026)
This study aims to analyze the effectiveness and contribution of Certain Goods and Services Tax (PBJT) on Arts and Entertainment Services, Parking Services, and Rural and Urban Land and Building Tax (PBB-P2), as well as to examine the optimization efforts implemented by the Bekasi City Regional Revenue Agency (Bapenda) to increase local tax revenue. A simple mixed-methods approach was employed by combining descriptive quantitative analysis and a qualitative case study. The research involved officials of the Bekasi City Regional Revenue Agency and selected taxpayers using purposive sampling. The findings indicate that the effectiveness of the three tax categories varied across the study period, while the contribution of PBJT remained relatively low compared to PBB-P2. The study also found that Bapenda optimized tax revenue through field supervision, taxpayer outreach, tapping box installation, and tax incentive programs to improve compliance and regional revenue.